Extracorporeal Shockwave Lithotripsy for Cystine Stones in Children: An Observational, Retrospective, Single-Center Analysis - Vinit, Nicolas; Khoury, Antoine; Lopez, Pauline; Heidet, Laurence; Botto, Nathalie; Traxer, Olivier; Boyer, Olivia; Blanc, Thomas; Lottmann, Henri B. (Frontiers in Pediatrics, 2021)
Purpose: Cystinuria is a genetic disorder characterized by a defective reabsorption of cystine and dibasic amino-acids leading to development of urinary tract calculi from childhood onward. Cystine lithiasis is known to be resistant to fragmentation. The aim was to evaluate our long-term experience with extracorporeal shockwave lithotripsy (ESWL) used as first line urological treatment to treat cystine stones in children. Methods: We retrospectively reviewed the charts of all children who underwent ESWL for cysteine stone. We assessed the 3-month stone-free rate, according to age, younger (group 1) or older (group 2) than 2 years old. Results: Between 2003 and 2016, 15 patients with a median (IQR) age at first treatment of 48 (15-108) months underwent ESWL in monotherapy. Median age was respectively 15 and 108 months in each group. The median (IQR) stone burden was 2620 (1202-8265) mm3 in group I and 4588 (2039-5427) mm3 in group II (p=0.96). 11 patients had bilateral calculi. ESWL was repeated on average 2.4 times, with a maximum of 4 for patients of group I and 4,8 times, with a maximum of 9 for group II (p>0,05). ESWL in monotherapy was significantly more efficient to reach stone free status for children under 2 years of age: 83% vs 6.2% (p=0,040). The median (IQR) follow-up of the study was 69 (42-111) months. Conclusion: ESWL appears as a valid urological option for the treatment of cystine stones, in young children. Even if cystine stones are known to be resistant to fragmentation, we report 83% of stone free status at three months with ESWL used in monotherapy in children under 2 years old with cystinuria. In older children the success rate is too low to recommend ESWL as a first line approach.